Religius Values in Novel Nafsul Muthmainnah by Anfika Noer - Nur Irwansyah (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study aims to describe religious values in the novel Nafsul Muthmainnah by Anfika Noer. The religious values analyzed include regulatory aspects (sharia), beliefs (creeds), and actions (morals). The approach used, namely the qualitative approach and the method used in this study is a descriptive analysis method. The use of this method is adjusted to the main purpose of the research, which is to describe and analyze religious values in a novel entitled Nafsul Muthmainnah by Anfika Noer. Descriptive method is a method used to describe or analyze a research result but not used to make broader conclusions. The purpose of this descriptive study is to make a description, description, or painting systematically, factually and accurately about the facts, traits, and relationships between phenomena investigated. The content analysis method is able to uncover the tendency of message content based on the context of the content of a text. The depth of content analysis will be more complete and detailed in understanding the contents of the text and able to associate with the context of reality that occurs. In this study, data information analysis was carried out through the stages of identifying all data, describing data, analyzing data, then interpreting existing data based on religious values in the novel. Conclusions from this study, namely that there are many religious values related to regulations (shari'a), beliefs (creeds), and actions (morals) in the Nafsul Muthmainnah novel by Anfika Noer's work. The religious values contained in this novel, namely aspects of sharia as many as 13 data findings, aspects of faith as many as 21 data findings, and moral aspects as many as 42 data findings. The most finding data is the moral aspect as many as 42 data findings and the least is the sharia aspect of 13 data findings.